'Two Birds with One Stone' design for dendrite-free zinc-metal anodes: Three-dimensional highly conductive skeletons loaded with abundant zincophilic sites. (October 2022) - Wang, Ran; Wu, Liyun; Wei, Ying; Zhu, Kaiping; Wang, Han; Yao, Yagang
Abstract: Aqueous zinc-metal batteries (Zn) have broad commercial application prospects owing to their large theoretical capacity, environmental friendliness, safety, and cost-effectiveness. However, the development of such batteries is limited by the growth of Zn anode dendrites. In this study, a highly conductive three-dimensional carbon fibers (CFs) skeleton with super-zincophilic ZnO preplaced on the surface (ZnO&CFs) was used to prepare Zn anodes. ZnO was expected to induce Zn nucleation and retard dendrite generation, and the CFs skeleton was expected to decrease the local current density to homogenize Zn ion flow and relieve the bulk stress during charging and discharging. Multifunctional regulation of the novel anode was confirmed through density functional theory calculations and experimental characterization. Symmetric cells assembled from the ZnO&CFs deposited with Zn as anodes were stable for more than 2, 000 cycles at a high current density of 20 mA/cm 2 and exhibited a low overpotential (≈50 mV). These results indicated that the proposed three-dimensional skeleton composite anodes can effectively inhibit dendritic growth and prolong cell life, thereby facilitating the development of efficient and stable Zn anodes. Graphical abstract: Image 1 Highlights: The zincophilic sites induce zinc deposition. The conductive three-dimensional skeleton homogenizes the electric field. DFT calculations suggested the high zincophilicity of ZnO, and FEM showed a uniform electric field of ZnO&CFs. The symmetric cell based on Zn@ZnO&CFs was stably cycled for more than 2, 000 cycles at a current density of 20 mA/cm 2 .